Superoxide Anion Production by the Spermatozoa of Men with Varicocele: Relationship with Varicocele Grade and Semen Parameters - YÜKSEL, MERAL (KOREAN SOC SEXUAL MEDICINE & ANDROLOGY, 2018)
Purpose: To investigate the pathophysiological role of superoxide anion and total reactive oxygen species (ROS) production by the spermatozoa of men with varicocele and its relationship with varicocele grade and semen parameters. Materials and Methods: This prospective study included 34 men with grade II-III varicocele, regardless of their fertility status. The control group consisted of 13 healthy men. Semen characteristics were examined according to the 2010 World Health Organization criteria. The swim-up method was used for sperm preparation. Total ROS and superoxide anion production was assayed by luminol-and lucigenin-dependent chemiluminescence (CL), respectively. Results: The men with varicocele had significantly higher total ROS and superoxide anion levels than the healthy control subjects (2.9 +/- 0.4 relative light unit (RLU) vs. 2.4 +/- 0.1 RLU, p=0.001 for luminol-dependent CL and 2.8 +/- 0.4 RLU vs. 2.3 +/- 0.2 RLU, p=0.002 for lucigenin-dependent CL). Cases of grade III varicocele had significantly higher superoxide anion and total ROS levels than grade II cases and control subjects (p<0.001). Superoxide anion and total ROS levels were negatively correlated with all semen parameters. Conclusions: The superoxide anion levels produced by spermatozoa were significantly higher in varicocele patients than in control subjects. ROS production was related to increased varicocele grade, impaired semen concentration, and abnormal morphology in men with varicocele. Our findings suggest that superoxide anion overproduction may be an important step in the cascade of ROS-related damage to spermatozoa, resulting in impaired semen parameters in patients with varicocele.
Keywords: Oxidative stress; Reactive oxygen species; Spermatozoa; Superoxides; Varicocele; OXIDATIVE STRESS; INFERTILITY; PATHOPHYSIOLOGY; FRAGMENTATION; PATHOGENESIS; GENERATION; DIAGNOSIS; CRITERIA; HYPOXIA